Long-term impact of adolescent chronic pain on young adult educational, vocational, and social outcomes - Murray, Caitlin B; Groenewald, Cornelius B; de la Vega, Rocio; Palermo, Tonya M (Pain (Amsterdam), 2020)
Despite evidence of broad impact on daily functioning in adolescence, little is known regarding the life course effects of childhood chronic pain. This is the first nationally representative study to characterize the disruptive impact of chronic pain in adolescence on key educational, vocational, and social outcomes in young adulthood (12 years later). Data from the National Longitudinal Study of Adolescent to Adult Health (Add Health) were used, including 3174 youth with chronic pain and 11,610 without chronic pain. Multivariate regression analyses controlling for sociodemographic factors and adolescent depression found that chronic pain in adolescence was associated with long-term risk of a constellation of impairments indicative of socioeconomic disparities. Specifically, adolescent chronic pain was subsequently associated with reduced educational attainment (eg, lower odds of attaining a high school diploma and bachelor's degree), poor vocational functioning (eg, lower odds of receiving employer-provided benefits and higher odds of receiving public aid), and social impairments (eg, early parenthood, lower self-reported romantic relationship quality) in young adulthood. These findings provide a window into the future of adolescents with chronic pain, contributing to the limited knowledge base of the scope of adverse long-term outcomes during the transition to adulthood. However, several questions remain. Increased research attention is needed to understand the life course impact of pediatric chronic pain, including early risk factors and underlying mechanisms that drive adverse outcomes as they unfold across the lifespan.